KEPUASAN MEMEDIASI PENGARUH SERVICE QUALITY PADA LOYALITAS DEBITUR PD. BPR BKK KARANGMALANG CABANG MASARAN SRAGEN - Esa, Zanuar Krisna Wahyu (-)
The as purpose of this study to determine, analyze and test empirically of satisfaction mediate the influence of service quality on loyalty of debtors PD. BPR BKK Karangmalang Branch of Sragen. The analytical technique used is by using instrument test which includes validity test and reliability test, linearity test, regression analysis, path analysis, t test, F test, coefficient determination test and correlation analysis. Test result t in the first equation can be concluded that the variable of physical evidence, guarantee and empathy have positive and significant effect on debtor satisfaction and reliability have negative and significant effect on debtor satisfaction. While for the variable of responsiveness and empathy have a negative and insignificant on the satisfaction of the debtor. The result of t test on the second equation can be concluded that physical evidence, reliability, responsiveness, assurance, empathy and satisfaction have positive and significant effect on loyalty. F test results can be concluded together independent variables namely physical evidence, reliability, responsiveness, guarantee, empathy and satisfaction have significant effect on the loyalty of the debtor. Total R2 value of 0.978, can be interpreted variations of loyalty of debtors in PD. BPR BKK Karangmalang Branch of Sragen Masaran explained by debtor satisfaction variable and service quality of 97.8%, the remaining 2.2% described other variables outside the research model. The result of path analysis shows that the influence of physical evidence on debtor loyalty through debtor satisfaction is lower than direct influence, so more effective chosen direct path. The influence of reliability on the debtor's loyalty through the debtor's satisfaction is less than the direct influence, so the more effective the direct path is chosen. The influence of responsiveness on the debtor's loyalty through the debtor's satisfaction is less than the direct influence, so the more effective the direct path is chosen. The effect of the guarantee on the debtor's loyalty through the debtor's satisfaction is less than the direct influence, so the more effective the direct path is chosen. The influence of empathy on the debtor's loyalty through the debtor's satisfaction is less than the direct influence, so the more effective the direct path is chosen.Keywords: Service Quality, Satisfaction, Debtor Loyalty